2004
DOI: 10.1152/ajplung.00026.2004
|View full text |Cite
|
Sign up to set email alerts
|

Wnt-responsive element controls Lef-1 promoter expression during submucosal gland morphogenesis

Abstract: Regulated expression of lymphoid enhancer factor 1 (Lef-1) plays an obligatory role in the transcriptional control of epithelial bud formation during airway submucosal gland and mammary gland development. However, regions of the Lef-1 promoter required for spatial and temporal regulation during glandular development have yet to be defined. We hypothesized that a previously reported 110-bp Wnt-responsive element (WRE) in the Lef-1 promoter, which can be induced by Wnt-3a/beta-catenin signals, may also play a ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 35 publications
5
47
0
Order By: Relevance
“…The shorter Lef-1 isoform is produced from a second (P2) promoter located in the second intron of the LEF-1 locus (27,30,34). Recent studies have shown that the LEF-1 promoter is transcriptionally responsive to Wnt/Tcf/␤-catenin induction (12,18,34). PITX2 and Lef-1 interact independently of ␤-catenin.…”
Section: Discussionmentioning
confidence: 99%
“…The shorter Lef-1 isoform is produced from a second (P2) promoter located in the second intron of the LEF-1 locus (27,30,34). Recent studies have shown that the LEF-1 promoter is transcriptionally responsive to Wnt/Tcf/␤-catenin induction (12,18,34). PITX2 and Lef-1 interact independently of ␤-catenin.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a number of signaling pathways (including those involving wingless 1 int-1 [Wnt], bone morphogenetic protein [BMP], fibroblast growth factor [FGF] Notch, and Hedgehog) and their downstream effectors or modulators have been identified as important mediators of cell-fate specification during the morphogenesis of glandular organs. For example, the HMG-box transcriptional factor lymphoid enhancer binding factor (Lef-1) of the Wnt pathway is involved in the initiation of the development of SMGs and a wide range of other epithelial, bud-forming organs, including mammary glands, teeth, and hair follicles (37)(38)(39)(40)(41). Like Lef-1, other transcription factors, such as Pax6 and Msx1/2, have been shown to be involved in bud formation of glandular organs (42,43).…”
Section: Molecular Mechanisms That Specify Formation Of the Smg Stem mentioning
confidence: 99%
“…Mice lacking the Lef-1 gene are impaired in bud formation of the mammary gland, tooth, vibrissa, hair, and airway/nasal SMGs, suggesting that Lef-1 expression is required for formation of these organs (38)(39)(40)(41). In the context of airway SMG development, expression of Lef-1 at both the mRNA and protein levels is highly induced during the early bud stage, in which three to five cells aggregate within the surface epithelium before invagination (37)(38)(39)(40). During later stages of gland development, Lef-1 expression is restricted to the cells in the most distal invading tips of the tubules.…”
Section: Molecular Mechanisms That Specify Formation Of the Smg Stem mentioning
confidence: 99%
See 2 more Smart Citations